Influence of Water Content on Biofiltration Performance - Daisy B Badilla; Peter A Gostomski; Maria Lourdes P Dalida (ASEAN Journal of Chemical Engineering, 2010)
In biofiltration, contaminants in a gas stream are transferred into a biofilm on the filter bed medium and are metabolized by the microorganisms. Water is essential for microbial growth/activity and for transport of nutrients. In both full-scale and laboratory-scale systems, the water content of the medium is difficult to control. In this study, a biofilter, with rigorous water content control and internal gas recycle, was used to determine the influence of the water content on the degradation of toluene. Soil was used as the medium for treating toluene-contaminated air at an average inlet concentration of 263 ppm and a flow rate of 21 ml min-1. Through a water retention curve, gravimetric water content was related to matric potential. Results showed that lowering the water content from 79 to 48% (dry weight) or -20 to -400 cm H2O matric potential decreased the elimination capacity (EC) by 42% (29.8 to 17.3 g m-3h-1). Wetting the medium by increasing the matric potential from -400 to -10 cm H2O increased the elimination capacity to 43.9 g m-3h-1. However, further increase of the matric potential from -10 to -5 cm H2O decreased the elimination capacity by 57% (43.9 to 19.0 g m-3 h-1). Thus, this study suggests the soil water content should be controlled at about 96% (dry weight) or a matric potential of -10 cm H2O and the maximum elimination capacity is restricted to a narrow water content/matric potential. This narrow range impacts on the operation of full-scale biofilters as traditional techniques for water content control would make maintaining this range difficult.